2009
DOI: 10.1590/s0104-42302009000600013
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with low birth weight in a historical series of deliveries in Campinas, Brazil

Abstract: SummaryObjective. To identify the risk factors associated with low birth weight (<2500 grams). MethOds. Unmatched case-control study performed in a tertiary maternity hospital in Campinas, Brazil, involving 43,499 liveborn infants delivered in the institution between 1986 and 2004. Analysis of the database containing information on deliveries of women who gave birth to infants with low (6,477 cases) and normal (37,467) birth weight were performed. Factors associated with low birth weight were identified accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
3
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 21 publications
6
25
3
11
Order By: Relevance
“…The number of LBW neonate in male, female and ambiguous was 50,569, 55,972 and 386 also the percentage of LBW births in male, female and ambiguous was 6.5, 7.7 and 53.9 respectively. The total incidence of LBW in the present study is substantially lower than that reported in India and Brazil (14.7%) [5] [14], it was close to the incidence rate in New York State, which was 8.2% in 2009 and the nationwide U.S. average, as reported by 246 medical centers throughout the country 2005 (3.8% -10.6%) [3] [15].…”
Section: Discussionsupporting
confidence: 67%
“…The number of LBW neonate in male, female and ambiguous was 50,569, 55,972 and 386 also the percentage of LBW births in male, female and ambiguous was 6.5, 7.7 and 53.9 respectively. The total incidence of LBW in the present study is substantially lower than that reported in India and Brazil (14.7%) [5] [14], it was close to the incidence rate in New York State, which was 8.2% in 2009 and the nationwide U.S. average, as reported by 246 medical centers throughout the country 2005 (3.8% -10.6%) [3] [15].…”
Section: Discussionsupporting
confidence: 67%
“…Se os países da América Latina tivessem uma prevalência de restrição do crescimento fetal (RCF) similar à dos desenvolvidos, milhares de mortes infantis seriam evitadas por ano 2 . Além da prematuridade e da RCF, os estudos têm identificado também, como fatores determinantes do baixo peso fetal, a desnutrição materna, idade materna avançada, antecedentes de baixo peso e parto prematuro, baixo nível de escolaridade, nuliparidade, tabagismo e acompanhamento pré-natal insuficiente 3 .…”
unclassified
“…18 Sabe-se que a gestação em mulheres com 35 anos ou mais está associada ao risco aumentado para complicações maternas (maior ganho de peso, obesidade, diabetes mellitus, hipertensão arterial crônica, pré-eclâmpsia e miomas) e fetais e do RN (anormalidades cromossômicas e abortamentos espontâneos, mecônio intraparto, baixo peso ao nascer, restrição do crescimento fetal, macrossomia, sofrimento fetal, necessidade de internação em unidade de terapia intensiva e óbito neonatal). 6,19 Idade avançada, sobrepeso e ganho ponderal excessivo na gravidez são aspectos que influenciam os resultados obstétricos e, portanto, merecem atenção dos profissionais de saúde, no sentido de contribuírem para a redução da morbimortalidade materna e perinatal, bem como para a melhoria das condições do nascimento. Os fatores de risco precisam ser compreendidos e considerados, com vistas a melhorar o resultado da gravidez, além de prevenir a síndrome hipertensiva e o diabetes gestacional.…”
Section: Meu Pai Faleceu E Minha Mãe Ficou Muito Doentetive Dunclassified